PERAN MAHASISWA TERHADAP PEREKONOMIAN DI KOTA MALANG MELALUI KOPERASI MAHASISWA - Mursidi; M. Akbar, Dzikriyansyah; Aisyah Fitri, Azzahra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
This research aims to understand: 1) The role of students as millennial generationin the formation of awareness of the importance of cooperatives to improve the economyin Malang, 2) How the Malang City Cooperative Office accommodates students asmillennials to foster prosperity will support cooperatives, 3) How knowledge MalangCity community about cooperatives. This study uses qualitative research with the subjectof students as the generation and objects of the general public. Data collection usesinterview methods and historical data. The results showed that: 1) students must have awillingness or interest in cooperatives and have creative and innovative ideas or ideasto develop cooperatives in the general public, 2) Malang City Cooperative Office hasan important role by providing education, training and mentoring to special studentsmembers student cooperatives about, 3) community knowledge about cooperatives isvery little and does not trust cooperatives.